Double-layer micro porous media burner from lean to rich fuel mixture: Analysis of entropy generation and exergy efficiency - Ismail N.C.; Abdullah M.Z.; Mustafa K.F.; Mazlan N.M.; Gunnasegaran P.; Irawan A.P. (MDPI, 2023)
Porous media burner (PMB) is widely used in a variety of practical systems, including heat exchangers, gas propulsion, reactors, and radiant burner combustion. However, thorough evaluations of the performance of the PMB based on the usefulness of entropy generation, thermal and exergy efficiency aspects are still lacking. In this work, the concept of a double-layer micro PMB with a 23 mm cylindrical shape burner was experimentally demonstrated. The PMB was constructed based on the utilization of premixed butane-air combustion which consists of an alumina and porcelain foam. The tests were designed to cover lean to rich combustion with equivalence ratios ranging from ? = 0.6 to ? = 1.2. It was found that the maximum thermal and exergy efficiency was obtained at ? = 1.2 while the lowest thermal and exergy efficiency was found at ? = 0.8. Furthermore, the findings also indicated that the total entropy generation, energy loss, and exergy destroyed yield the lowest values at ? = 1.0 with 0.0048 W/K, 98.084 W, and 1.456 W, respectively. These values can be stated to be the suitable operating conditions of the PMB. The findings provided useful information on the design and operation in a double-layer PMB. 2021 by the authors. Licensee MDPI, Basel, Switzerland.